2021
DOI: 10.2147/opth.s342682
|View full text |Cite
|
Sign up to set email alerts
|

Influence of COVID‑19 on the Prognosis and Medication Compliance of Glaucoma Patients in the Nile Delta Region

Abstract: Objective: To assess the influence of the COVID-19 pandemic on the medication adherence and follow-up of glaucoma patients in the Nile Delta region. Setting: A tertiary care center in the Nile Delta region, Egypt. Study Design: An observational, cross-sectional study. Participants: Patients' records (2019-2020; group A) and (2020-2021; group B) were assessed for missed follow-up visits, medication adherence, number of trabeculectomies performed, and uncontrolled patients. In addition, a telephone-based questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…This study revealed that the financial restriction (21.5% of participants) was the biggest barrier to non-medication adherence among 200 patients with glaucoma. 42 In general, people with chronic diseases are often prescribed different long-term types of medication, so the high costs of their medication regimens are common. Thus, the affordability of medication has become an issue since insurance policy and coverage for medications are different at the individual and healthcare system levels.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that the financial restriction (21.5% of participants) was the biggest barrier to non-medication adherence among 200 patients with glaucoma. 42 In general, people with chronic diseases are often prescribed different long-term types of medication, so the high costs of their medication regimens are common. Thus, the affordability of medication has become an issue since insurance policy and coverage for medications are different at the individual and healthcare system levels.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, emerging evidence suggests that the pandemic has indubitably disrupted health behaviour among glaucoma patients worldwide. 18,[21][22][23][24][25] In particular, the patients' adherence has been adversely influenced, exacerbating already known barriers and manifesting new problems specific for the continuous period. 21,24 Concerning the pandemic-related problems, this study was conducted to assess the treatment adherence and identify the predictors of adherence among glaucoma patients treated at Zagreb University Hospital Center during the COVID-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…18,[21][22][23][24][25] In particular, the patients' adherence has been adversely influenced, exacerbating already known barriers and manifesting new problems specific for the continuous period. 21,24 Concerning the pandemic-related problems, this study was conducted to assess the treatment adherence and identify the predictors of adherence among glaucoma patients treated at Zagreb University Hospital Center during the COVID-19 outbreak. The study's secondary goal was to determine the main reasons for non-adherence to glaucoma treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations